'Children Are to Be Regarded as Propaganda': Contradictions of German Occupation Policies in the Child Evacuations to Switzerland, 1941–1942. (January 2021) - Sambells, Chelsea
During the first year of Nazi occupation in Belgium, the German authorities consented to send thousands of hungry children to neutral Switzerland for three-month periods of recuperation by means of a Swiss-operated evacuation scheme. After Nazi officials in Berlin learned of these unusual evacuations, the German occupation authorities in Belgium became embroiled in defending and justifying their actions. This article argues that while such contradictions and paradoxes in occupation policies epitomized the Nazi leadership, both the value and agency of children – and the perception of saving them – became unconventional Nazi weapons of exploitation and control.